FLORES: for exploring land use options in forested landscapes - Vanclay, J.K. (1998)
Incentives intended to stimulate better land use practices often don't work as intended, and can have undesirable side effects that were not foreseen. How can we better equip policy makers and their advisors to envisage fully the efficacy and consequences of initiatives? One way is to provide a decision support system. The formulation and construction of such a system offers other benefits: it would make existing information more accessible, facilitate hypotheses testing, and foster collaboration between researches working on these issues. FLORES is such a system being develop through a partnership coordinated by the Center for International Forestry Research